Évolution de la fertilité post-partum, de la folliculogénèse et des taux sériques de progestérone chez les juments Barbe, Arabe-Barbe et Pur-Sang Arabe du Haras de Tiaret. - BARKA Mohammed (My University, 2015)
In order to optimize the fertility of mares, the first postpartum ovulation requires special attention to the follicular dynamics. In the first part of our work, 37 Purebred Arabian mares and 13 mares barber aged 05-25 years and weighing 350-450 kg foaled. They were subjected to ultrasound scans of the ovaries from the 5th day post-partum prognosis of ovulation and pregnancy diagnosis. For against, the experiment conducted in the second part of our study is to assess the profile of serum progesterone in the 03rd to the 21th week of gestation. It involved a staff of 20 Purebred Arabian mares, 02 mares race barber and 02 Arabian barber mares aged 05-21 at level National Stud (chaouchaoua) Tiaret (Algeria).The progesterone assay is based on the technology of micro-particulate enzyme immunoassay (MEIA). Ultrasound explorations of Purebred Arabian mares and barber showed a fertility rate of 34.48% vs 42.85%, respectively. The subsequent average diameter of preovulatory follicles is 45.48 vs 41.82 mm, influenced by a combinatorial effect of race and age (P <0.001). Weekly dosage, enzyme immunoassay of progesterone during the first third of gestation, showed a higher rate with 02ng/ml gradually decrease from the 14th week of gestation. Optimization of fertility heat involves mastering the factors mentioned previously.
Keywords: postpartum, Purebred Arabian mares, barber, Arabian barber, fertility, preovulatory follicles, micro-particulate enzyme immunoassay (MEIA), progesterone.